Pituitary Gland: Normal Function and Assessment - Deepa Kirk; Kathryn W. Smith (Association of American Medical Colleges, 2016)
Abstract Introduction This computer-based, interactive module introduces preclinical medical students to normal pituitary function and outlines its assessment. Solid understanding of these topics is requisite to learning clinical disorders of the pituitary. Existing resources largely target learners at earlier or later stages of training; thus, we created this resource to address needs of medical students during a first- or second-year endocrine course. Methods A module format was selected to promote interactive, independent learning. Two cohorts of medical students completed the 40-minute module: 172 second-year students who had completed a year of basic sciences in the traditional curriculum and 180 foundation-phase students in a three-semester combined basic and clinical sciences curriculum (due to a change in the medical school curriculum at our institution). In both instances, the module was completed before start of clinical pituitary content. A static set of PowerPoint slides accompanied the module to facilitate note taking. Test Your Knowledge slides were inserted to ensure grasp of key terms/concepts before moving to subsequent slides. A short question-and-answer session was held following module completion to clarify points of confusion. Results Students rated effectiveness of the module as 4.6 out of 5, commenting on its clarity, organization, high-yield nature, and utility in preparing for clinical material. Faculty noted greater understanding of foundational pituitary principles and more engaging discussions. The percentage of pituitary-related questions answered correctly on the midterm exam increased. Discussion The success of the pituitary module prompted development of adrenal, thyroid, and parathyroid modules that now comprise the Endocrine Organs Introduction Series in our curriculum.